Putting It All Together: Creating and Scaling Exceptional Learning - Galle, Jeffery W.; Galle, Jo K. (Rowman & Littlefield Publishers, 2023)
Thanks to learning science and to the creativity of teaching and learning professionals, we know much more about the ways students learn experientially and collaboratively. For our courses, teaching scholars have identified practices and pedagogies that engage students to collaborate and experience deeper learning. Ken Bain has called Super Courses the courses that possess opportunities for learning in the classroom, the lab, and into the world where experiential learning joins course content. The course practices and pedagogies so fundamental to deep learning should also be included in program design (both for academics and campus life) and even the curriculum itself. Putting it all Together provides a frame that includes the pedagogies and practices and discussion of the larger contexts within which they can be applied. The book also offers more than thirty brief chapters of selected practices applied in individual contexts. The authors are faculty members, administrators, and staff professionals who have developed learning experiences for students. The rationale behind the book is simple: embedding the most powerful practices and pedagogies within courses, programs, and the curriculum calls for every professional at every institution to play a different but equally important role in improving student learning and student success.